2009
DOI: 10.1016/j.juro.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Percutaneous Tibial Nerve Stimulation for Different Types of Lower Urinary Tract Dysfunction in Children

Abstract: Percutaneous tibial nerve stimulation is reliable and effective for nonneurogenic, refractory lower urinary tract dysfunction in children. Efficacy seems better in dysfunctional voiding than in overactive bladder cases. There is evidence that percutaneous tibial nerve stimulation should be part of the pediatric urology armamentarium when treating functional incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
20

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 16 publications
2
53
1
20
Order By: Relevance
“…71 Percutaneous tibial nerve stimulation (PTNS) has been associated with positive results in uncontrolled studies. 72 In 2015, two groups published randomized, sham-controlled tri-als using a transcutaneous approach, therefore, dismissing the need for the percutaneous needle insertion. Though Patidar et al reported a cure rate of 67% and an improvement rate of 24% in the PTNS group, compared to 0% and 6%, respectively, in the sham group, 73 Boudaoud et al noted a similar clinical efficacy between their PTNS and sham groups.…”
Section: Neuromodulationmentioning
confidence: 99%
“…71 Percutaneous tibial nerve stimulation (PTNS) has been associated with positive results in uncontrolled studies. 72 In 2015, two groups published randomized, sham-controlled tri-als using a transcutaneous approach, therefore, dismissing the need for the percutaneous needle insertion. Though Patidar et al reported a cure rate of 67% and an improvement rate of 24% in the PTNS group, compared to 0% and 6%, respectively, in the sham group, 73 Boudaoud et al noted a similar clinical efficacy between their PTNS and sham groups.…”
Section: Neuromodulationmentioning
confidence: 99%
“…Depuis, plusieurs séries pédiatriques ont été publiées sur la stimulation transcutanée parasacrale (électrodes de surface) [7-10] et sur la stimulation percutanée tibiale postérieure (aiguille) [11][12][13]. Les principales caractéristiques de ces études ont été recensées dans le Tableau 2.…”
Section: Discussionunclassified
“…Dans [7][8][9][10][11][12][13]. Dans notre étude, nous avons évalué l'efficacité sur le ressenti clinique du patient et sur le calendrier mictionnel.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The nonneurogenic cohort responded much better than the neurogenic individuals (78% of the non-neurogenic children experienced "some benefit," compared with 14% of the neurogenic children). The children were observed for 2 years and required chronic monthly stimulation to retain the benefit [26].…”
Section: Parkinson's Diseasementioning
confidence: 99%